EXPLORING THE PEDAGOGICAL POTENTIAL OF YOUTUBE IN ARABIC LANGUAGE EDUCATION: A MULTIDISCIPLINARY PERSPECTIVE - Zahroh, Tabassum Aliyatuz (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Learning is an aspect that continues to grow in tandem with technological advancements. One significant technological growth in the field of education is the use of online platforms. One pionering platform in providing multimedia content is YouTube. Arabic language teachers face their own challenges in conducting teaching and learning activities. These difficulties arise because Arabic is not the basic language of the Indonesian society from birth. This research employs a qualitative descriptive analysis method, with a qualitative approach. The study is conducted at MTsN 7 Tulungagung. Data collection is carried out through observations of the learning process using the YouTube application for Arabic language instruction. The observation results show that the response of students at MTsN 7 Tulungagung to the use of the YouTube application in Arabic language learning is generally positive. Students demonstrate a high level of engagement during the learning sessions, indicating a significant interest in the material presented through videos. The research findings indicate several positive impacts of using the YouTube application in improving Arabic language speaking, listening, and writing skills, commonly referred to as maharah kalam, maharah istima', and maharah kitabah